2017
DOI: 10.1021/acs.energyfuels.6b03078
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Chemical Looping Combustion of CO with CaSO4-CaO Oxygen Carrier

Abstract: CaSO4 is an interesting alternative oxygen carrier for chemical looping combustion (CLC). Utilization of a CaSO4 oxygen carrier suffers deactivation caused by sulfur loss. To prevent sulfur loss, a small amount of CaO particles were mixed with the CaSO4 oxygen carrier. The predominant regions of CaSO4, CaS, and CaO have been obtained with consideration of SO2 and COS emissions. The predominant region of CaO is increasing with the temperature and CO2 partial pressures. Isothermal as well as nonisothermal kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To well address the initiation of CaSO 4 as an OC by inhibition of the sulfur release and amelioration of its reactivity over the cycles, two approaches have been applied. One practice is the addition of limestone, 11,15 CaCO 3 , 16 or CaO 17,18 as the sorbent to capture sulfur and decrease its release during the reduction/oxidation process. Zheng et al 18 investigated the performance of the CaSO 4 −CaO OC during CLC, and the results showed that the CaO additive could not only improve the CO 2 yield but also capture SO 2 and COS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To well address the initiation of CaSO 4 as an OC by inhibition of the sulfur release and amelioration of its reactivity over the cycles, two approaches have been applied. One practice is the addition of limestone, 11,15 CaCO 3 , 16 or CaO 17,18 as the sorbent to capture sulfur and decrease its release during the reduction/oxidation process. Zheng et al 18 investigated the performance of the CaSO 4 −CaO OC during CLC, and the results showed that the CaO additive could not only improve the CO 2 yield but also capture SO 2 and COS.…”
Section: Introductionmentioning
confidence: 99%
“…What is worse is that increasing the operating temperature would singly exacerbate the emission of sulfur from CaSO 4 via the side reactions of eqs – below. , Sulfur released not only led to atmospheric pollution but also tarnished the purity of outlet CO 2 and declined the reactivity of CaSO 4 . To well address the initiation of CaSO 4 as an OC by inhibition of the sulfur release and amelioration of its reactivity over the cycles, two approaches have been applied. One practice is the addition of limestone, , CaCO 3 , or CaO , as the sorbent to capture sulfur and decrease its release during the reduction/oxidation process. Zheng et al investigated the performance of the CaSO 4 –CaO OC during CLC, and the results showed that the CaO additive could not only improve the CO 2 yield but also capture SO 2 and COS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CaSO 4 –CaS–CaO phase diagram predicts that CaS is stable at the high partial pressure of sulphurous gas and reducing gas H 2 /CO using gaseous fuel. 32,33 Tian et al 33 observed that the solid product was almost pure CaS when the partial pressure of CO or H 2 was higher than 40 kPa. However, the side reactions generating sulphurous gas are unavoidable in the fuel reactor due to the aim of minimizing the unconverted products such as H 2 , CO and CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The SO 2 liberation from CaS oxidation may be trapped by CaO additive via reaction . In CLC with a CaSO 4 -based oxygen carrier, such as CaSO 4 , , CaSO 4 –Fe 2 O 3 , , CaSO 4 –NiO, CaSO 4 –CuO, and CaSO 4 –CaO oxygen carriers, the problem of sulfur emission occurs. In the literature, it has been proposed that the sulfur release should be captured by adding lime and limestone sorbent in the fuel reactor of the CLC system.…”
Section: Introductionmentioning
confidence: 99%